2014
DOI: 10.1118/1.4896824
|View full text |Cite
|
Sign up to set email alerts
|

T1‐weighted MR image contrast around a cryoablation iceball: A phantom study and initial comparison with in vivo findings

Abstract: The hyperintense rim around the iceball in fast T1w GRE images corresponded to cooled but nonfreezing temperatures (<20 °C) proximal to the frozen zone. The same image contrast was observed both in a phantom study as well as in vivo in the human prostate during cryotherapy. Potentially, monitoring of this rim could be useful in order to maintain a safe margin from at-risk tissues during MR-guided prostate cryoablation procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Cryoablation was performed using an MR-compatible cryoablation device (MRI-SeedNet; Galil Medical, Yokneam, Israel). Two 10-min freezing cycles separated by 2-min passive and 1-min active thaw were applied under continuous T1-weighted gradient echo MR monitoring [ 21 , 22 ]. The intraprocedural images were used to modulate the size and shape of the iceball by regulating the gas flow to each individual cryoprobe so as to cover the entire tumour while avoiding contact between the iceball and rectal wall.…”
Section: Methodsmentioning
confidence: 99%
“…Cryoablation was performed using an MR-compatible cryoablation device (MRI-SeedNet; Galil Medical, Yokneam, Israel). Two 10-min freezing cycles separated by 2-min passive and 1-min active thaw were applied under continuous T1-weighted gradient echo MR monitoring [ 21 , 22 ]. The intraprocedural images were used to modulate the size and shape of the iceball by regulating the gas flow to each individual cryoprobe so as to cover the entire tumour while avoiding contact between the iceball and rectal wall.…”
Section: Methodsmentioning
confidence: 99%
“…Recently interest has also revived in the use of MR-thermometry for monitoring cryoablations [24,136] and the temperature of adipose tissue [37,55,74,81,137]. When T 1 is used to monitor ablations of fatty tissue such as breast, water must be suppressed [138] or water and fat signals separated [55,77] for improved accuracy.…”
Section: Limitations In Methods Based On the Temperature-dependence Omentioning
confidence: 99%
“…The most commonly treated tissue is the liver; however with advances in equipment for delivery of thermal energy [5,7,11,14,28,[30][31][32], accurate temperature monitoring, image reconstruction and automation [3,4,6,8,9,[11][12][13][15][16][17][23][24][25], the possibilities are expanding. Emerging applications include local drug-delivery [112][113][114], epilepsy treatment [9], quality control of red blood cells [115], iron mapping [116], diagnosis of multiple sclerosis [117], and brain abnormalities [118,119] and identification of iron-oxide labelled stem cells [120].…”
Section: Introductionmentioning
confidence: 99%
“…Iceball growth can be monitored in near real time with T1 weighted gradient echo imaging [62]. Overduin et al [63] reported that a hyperintense rim is seen progressing at the margins caused by shortening of T1 and seen in cooled (less than 20 8C) but as yet nonfreezed margin. MR thermography information is less accurate from cooling tissue and is therefore not routinely used.…”
Section: Magnetic Resonance-guided Focal Cryoablationmentioning
confidence: 98%